2015
DOI: 10.2196/medinform.4640
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time and Retrospective Health-Analytics-as-a-Service: A Novel Framework

Abstract: BackgroundAnalytics-as-a-service (AaaS) is one of the latest provisions emerging from the cloud services family. Utilizing this paradigm of computing in health informatics will benefit patients, care providers, and governments significantly. This work is a novel approach to realize health analytics as services in critical care units in particular.ObjectiveTo design, implement, evaluate, and deploy an extendable big-data compatible framework for health-analytics-as-a-service that offers both real-time and retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As a proof-of-concept, the approach is illustrated through a clinical scenario of a healthcare team managing a patient with chronic kidney disease. In the domain of big data in healthcare, Khazaei et al [11] presented a cloud-based framework for big data analytics, supporting both real-time and retrospective analyses. The study introduces an architectural paradigm to implement health-analytics-as-a-service, which is currently a central theme in the era of big data in healthcare (e.g., a relevant effort is conducted in the H2020 AEGLE project, http://www.aegle-uhealth.eu/).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…As a proof-of-concept, the approach is illustrated through a clinical scenario of a healthcare team managing a patient with chronic kidney disease. In the domain of big data in healthcare, Khazaei et al [11] presented a cloud-based framework for big data analytics, supporting both real-time and retrospective analyses. The study introduces an architectural paradigm to implement health-analytics-as-a-service, which is currently a central theme in the era of big data in healthcare (e.g., a relevant effort is conducted in the H2020 AEGLE project, http://www.aegle-uhealth.eu/).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Khazaei et al [8] has proposed a cloud-based Health Analytics as a Service (HAaaS) framework that enabled Artemis to be offered as an Artemis Cloud HAaaS. In that framework, the Data Acquisition component of Artemis can be located at a different location to the remaining Artemis components which are provisioned through cloud services.…”
Section: Artemis Cloudmentioning
confidence: 99%
“…This notable increase in mortality rate and annual health care expenditure (affected by the increased length of stay) has made sepsis treatment and research a critical domain in medical internet research and medical informatics, resulting in a recent surge in the related literature [21][22][23][24]. Studies have shown that improved and effective methods of early sepsis identification can substantially reduce the severity and epidemiological burden of sepsis in the United States [24][25][26][27][28][29]. In addition, several authors have recommended that identifying the prevalent risk factor(s), followed by an instant diagnosis, can reduce the cost in treatment workflow, and further scale down the mortality rate for patients with sepsis to some extent [26,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%